METHODOLOGIES FOR CREATING ONTOLOGIES - de Oliveira, Marcus Rogério (Revista Interface Tecnológica, 2012)
Recording, transmitting and consulting the knowledge in computers with application of inferences and reasoning made by computerized agents requires knowledge structured in formals constructions and standardized constraints called Ontologies. The data representing the knowledge formalized in Ontologies must be organized in data structures with some software requirements. Many researchers have proposed and designed concepts, applications and tools for Ontologies with different requirements. This paper discusses a historical approach on ontology, its philosophical aspects and principles and addresses their main methodologies for creation.
Keywords: Ontologies; Philosophy; Knowledge; Methodology